To investigate the effectiveness of human resource management for organizational success - Syarina, binti Sajali (Universiti Malaysia Sarawak (UNIMAS), 2012)
Over the last decade, much research has been conducted in the field of human resource management (HRM) and its associations with firm performance. The purpose of this study is to investigate the effectiveness ofHR department towards organization success. This study examines the effectiveness of HRM practices towards the beneficial of the employee and also the employer. Data were collected by hand from selected state government agencies, government linked company, private company and a multinational corporation to get the different ideas and practices of human resource management. This study is focusing in Kuching area where research had been conducted at Land Custody Development Corporation, MEMC Kuching Sdn. Bhd., Nairn Cendera Sdn. Bhd. and Craun Research Sdn. Bhd. A total of 100 useable responses were obtained and used for the purpose of analysis. The results are analyzed by using descriptive statistics which is "frequencies" as the analytical techniques. The findings can form the basis for useful recommendations for Malaysian managers in encouraging the practice of human resource management and for employees who are concerned with the effectiveness level of their Human Resource department for long-term organizational success.